The First Russian Conference with International Participation «Malignant Tumors Associated with HPV. Primary Prevention and Screening» - Article Editorial (Эпидемиология и вакцинопрофилактика, 2019)
The First Russian Conference with International Participation «Malignant Tumors Associated with HPV. Primary Prevention and Screening».